EVALUASI PENERAPAN IMBALAN PASCA KERJA (PENERAPAN PSAK 24 REVISI 2015) PADA PT XYZ - Rusdiyanto, Rusdiyanto; Saraswati, Fitria (GEMA EKONOMI, 2018)
Indonesian Institute of Accountants has issued accounting standard regarding Employee Benefits. These Standards contained in Statement of Financial Accounting Standards No.24 Revised 2015 about Employee Benefits. This research was conducted at the PT XYZ which would apply Statement of Financial Accounting Standards (PSAK 24) in the preparation of their financial statements. Employee benefit is an obligation which is owned any company that has a major influence on the company in terms of external stakeholders such as in this case the owner of the company or creditors and internal as workers will have a direct impact on corporate performance. Due to its major influence on the company in view of the need to conduct proper disclosure in accordance with accounting standards generally accepted. This study focuses on Post-Employment Benefits which is remuneration received by workers if the workers has stopped working. This study aimed to evaluate the accounting treatment in particular Employee Benefits PT XYZ whether in accordance with Statement of Financial Standards No.24 Revise 2015. The analytical method used is qualitative comparative which provides comparing what is applied by the company with what has been stipulated in Statement of Financial Accounting Standards No.24 Revised 201. Research in PT XYZ it can be concluded that the employment benefits at PT XYZ can be categorized into three categories based on PSAK 24 are employee benefit short-term, post-employment benefits, and severance and reporting are done on all three benefits are already in accordance with PSAK 24 2015. DOI : 10.5281/zenodo.3475721